HUBUNGAN FAKTOR INDIVIDU DAN BEBAN KERJA MENTAL TERHADAP KEPUASAN KERJA PERAWAT DI RUMAH SAKIT ISLAM JAKARTA SUKAPURA TAHUN 2022 - Dinda Bilah Salwah Cikal, (2023)
High job demands on nurses, such as increased patient visits, might unintentionally increase mental workload, which can be related to job satisfaction. This research aims to determine the association between individual factors and mental workload with job satisfaction among nurses at Jakarta Sukapura Islamic Hospital. This research used a quantitative method with a cross-sectional research design. The 72 research samples were selected by purposive sampling technique. This research used the Chi-Square test. The measurement tools used in this research are the NASA-TLX to measure mental workload and the Minnesota Satisfaction Questionnaire (MSQ) to measure job satisfaction. The results showed that 43.1% of nurses had low job satisfaction, and 50% of nurses had a heavy mental workload. There is a significant association between mental workload and nurse job satisfaction (p-value = 0.004) with POR = 4.71 (95% CI 1.71-12.93). The hospital is encouraged to minimize mental workload hazards by conducting seminars on how to control mental workload.